Molecular Identification of Family Colubridae from Punjab, Pakistan (Advances in Applied Biological Research, 2024)
The present one year study was extended from May 2019 to March 2020 was conducted in selected sites of Punjab. This study focuses on the molecular identification and morphometric analysis of two snake species, Platyceps rhodorachis (Cliff Racer) and Amphiesma stolatum (Buff Striped Keelback) collected from selected sites in Punjab, Pakistan. Each captured specimen was tagged with specific number and identified using morphological keys. Total genomic DNA was extracted from preserved tissues and amplified using COI primers set. After trimming ambiguous bases, the obtained COI fragments of Platyceps rhodorachis was 668 bp while fragments of Amphiesma stolatum was 639 bp. The COI fragments aligned with available sequence from NCBI comprised of 620 bp. The DNA sequences have shown reliable and exact species identification. The mean intraspecific identities of Platyceps rhodorachis (Cliff Racer) and Amphiesma stolatum (buff striped keelback) was 0.11±0.01 and respectively based of p-distance.  Different molecular markers have been used in this study. Platyceps rhodorachis and Amphiesma Solatum successfully amplified using COI gene. It can be concluded that, identification of reptiles on morphological basis is still considered authentic. However, large scale molecular analysis of these taxa is required for exact species identification and to report any new species from area.
Keywords: Platyceps rhodorachis; Amphiesma stolatum; mtDNA; COI; Cytb